Ethical imagination and the new possibilities of subjectivity: a global perspective on the culture of the self and its evolution in Kurdistan. Issue 6 (2nd November 2018) - Dastooreh, Kaveh
ABSTRACT: This paper is written with the hope of not only presenting an ethics that could speak to some of our contemporary subjective and ethical issues but also to introduce some of the pragmatic and aesthetic practices, as they are styled and heightened by a culture in Kurdistan that we call 'the culture of the self'. It was a culture of elaborating the self and it contained many elements of an ethical perspective. At the beginning of the twentieth century, this culture gradually gave way to a normative and moralistic one. What we acquire from this historical approach is the need to explore the possibility of the re-emergence of a new culture of the self that makes the conditions of subjectivity imaginable. Such a goal will be conceivable if any modern inspiration from 'the culture of the self' is to be realized under the direction of a 'creative' interpretation; an ethical imagination will be at the heart of this reflective culture.